Bilingual identity: issues of self-identification of bilinguals in Malaysia and Tatarstan - Broadbent, John T.; Vavilova, Zhanna (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2015)
Am I English when I speak English and Russian when I speak Russian if I use both equally well? Am I the same when I speak English and when I speak Russian? In what cases would I prefer to use which one of them? These questions are at the core of the issue of the identity of bilinguals, particularly if they suffer in any way from fragmented identity, linguistic interference, misunderstanding in a monolingual society and other related problems. This paper aims to look closely at these issues in certain bilingual environments in order to define the role of multilingualism in the self-identification of an individual. Reflecting on experience over forty years of teaching bilinguals, multilinguals and L2 English-speakers, we may draw the conclusion that anomie, identityconflict, results not from the experience of bilingualism or multilingualism per se but arises where anxiety and lack of self-confidence in one's own identity - either individually or collectively - is already present. It seems evident, then, that the root cause of alienation lies not in bilingualism itself but in the conflict of cultures. The implication appears to be that cultural self-identification governs language proficiency rather than is determined by it.